Anti-stress activity of different extracts of Caralluma fimbriata in wistar rats - Somayeh Afsah Vakili, Somayeh Afsah Vakili; Syed Fayazuddin, Syed Fayazuddin (International Journal of Indigenous Herbs and Drugs, 2018)
Objective: The current investigation was planned to assess adaptogenic activity of aqueous and ethanol extracts of Caralluma fimbriataMethods: Anti-stress of aqueous and ethanol extracts of Caralluma fimbriata was appraised by inducing stress in rats through the forceful swimming. Biochemical parameters such as 6-β-OH-cortisol, urinary vanillymandelic acid (VMA), homovanillic acid (HVA), ascorbic acid and 5-hydroxyindoleacetic acid (5HIAA) were estimated to analyze the anti-stress activity. Aqueous and ethanol extracts of Caralluma fimbriata were administrated orally at dose of 200 and 400 mg/kg body weight one h before the induction of stress to prevent stress-induced urinary biochemical changes in a dose dependent manner.Results: Nevertheless, in all groups which were treated with aqueous and ethanol extracts of Caralluma fimbriata, there was no statistically difference between level of 6-β-OH-cortisol, urinary vanillymandelic acid (VMA), homovanillic acid (HVA), ascorbic acid and 5-hydroxyindoleacetic acid (5HIAA) as compared to normal animals.Conclusion: The present investigation indicated that aqueous and ethanol extract of Caralluma fimbriata have potential anti-stress activity.